A rare case of solitary exostosis of capitate - Singh, Siddhartha; Singh, Amarendra Bahadur; Nishani, Manjunath; Verma, Mohit Kumar (International Journal of Research in Orthopaedics, 2024)
Exostosis arising from carpal bones is rare and only a few cases have been reported till date. A 29 years old female came to the outpatient department with a localized swelling present on the dorsum of her right wrist since the past three years. On examining the patient clinically, a well-defined protuberance was observed over the dorsal aspect of the right wrist. CT report showed bony outgrowth over the dorsum of the capitate extending beyond the carpometacarpal joint. In surgical intervention, the mass was removed from the base, which grossly had an appearance of chondral origin. The biopsy report confirmed the diagnosis of exostosis (osteochondroma). Hence, excising the exostosis surgically led to achievement of adequate motion of the patient’s wrist along with the additional cosmetic correction benefit.